2000
DOI: 10.1093/jac/45.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Serum itraconazole concentrations and clinical responses in Candida-associated denture stomatitis patients treated with itraconazole solution and itraconazole capsules

Abstract: The aim of this study was to compare the concentrations of itraconazole in serum and saliva after treatment with itraconazole cyclodextrin solution or itraconazole capsules in Candida-associated denture stomatitis patients without evidence of immunodeficiency. Forty patients were randomly assigned to receive either itraconazole cyclodextrin solution or itraconazole capsules, both at a dosage of 100 mg bd for 15 days. On completion of treatment palatal erythema was assessed and an oral rinse and imprint culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 7 publications
0
27
0
1
Order By: Relevance
“…We used serum levels of azole as an estimate of levels in the oropharynx. Previous studies found that levels in saliva were similar or higher than corresponding values in serum [22,23]. It is uncertain whether a peak or a trough level is the most important predictor of outcome.…”
Section: Discussionmentioning
confidence: 94%
“…We used serum levels of azole as an estimate of levels in the oropharynx. Previous studies found that levels in saliva were similar or higher than corresponding values in serum [22,23]. It is uncertain whether a peak or a trough level is the most important predictor of outcome.…”
Section: Discussionmentioning
confidence: 94%
“…Of the 35 included trials, 11 did not have data to be entered in the meta‐analysis because they presented the results only in figures or graphs or because the data were not usable for statistical analysis …”
Section: Resultsmentioning
confidence: 99%
“…The duration of the intervention in the majority of the studies was 14 to 15 days. 13,14,[16][17][18]22,[24][25][26][27]31,[35][36][37][38][39]42,43,45,46 Some were 7 to 8 days, 15,32,40,47 and the rest were longer than 15 days, with a maximum of 90 days. 11,12,20,21,23,[28][29][30]33,34,41,44 One study used a single application of the intervention.…”
Section: Characteristics Of the Interventionsmentioning
confidence: 99%
“…Studies examining the use of itraconazole for prophylaxis of invasive fungal infections in neutropenic patients have associated concentrations of 0.25-0.5 mg/L with efficacy [21][22][23]. Concentration breakpoints established as potential targets for successful treatment of invasive fungal infection range from 5 to 6.5 mg/L when measured by bioassay and 0.6-1 mg/L when measured by HPLC [19,[24][25][26][27][28]. There are a number of limitations associated with interpreting results of these studies, as they are retrospective, include a small number of patients, do not have standardized reasons or timing for obtaining concentrations, and are not designed to establish an ideal concentration target.…”
Section: Concentration-efficacy Relationshipmentioning
confidence: 99%